Preface - Nowak, Andrzej J.; Szczygieł, Ireneusz (Computer Assisted Methods in Engineering and Science; Vol 21 No 3-4 (2014), 2014)
This special issue of the Computer Assisted Methods in Engineering and Science comprises selected papers presented during the International Conference on Inverse Problems in Engineering 2014 (ICIPE2014). The ICIPE2014 Conference took place in Kraków in May 2014. The ICIPE2014 was the 24th in the series of national and international meetings on inverse problems that were initiated at Michigan State University in 1988. The 2014 edition was the 8th International Conference. Both the Scientific Committee members and the participants came from many countries all over the world: USA, Brazil, Russia, Poland and France among others.